The Civil War and Reconstruction : an eyewitness history - Kirchberger, Joe H. (New York : Facts on File, 1991)
Portrays the American Civil War and its aftermath through such primary sources as memoirs, diaries, letters, contemporary journalism, and official documents
Includes bibliographical references (p. 377-382) and index
Keywords: Reconstruction (U.S. history, 1865-1877) -- Sources; Reconstruction (U.S. history, 1865-1877) -- Chronology; United States -- History -- Civil War, 1861-1865 -- Personal narratives; United States -- History -- Civil War, 1861-1865 -- Chronology; United States -- History -- Civil War, 1861-1865 -- Sources; United States -- History -- Civil War, 1861-1865 -- Sources